ANALYSIS OF MATHEMATICAL LITERACY INCREASE AND LEARNING INDEPENDENCE THROUGH PROBLEM-BASED LEARNING - Dede Anggiana, Agus; Kandaga, Thesa; Hermawan, Vevi (Universitas Efarina, 2022)
Mathematical literacy ability is one of the abilities that must be possessed by students to solve problems in the form of word problems that are related to problems in the real world, so that find solutions to mathematical problems requires learning independence. The learning model that can improve mathematical literacy skills is the Problem-Based Learning (PBL) model. The PBL model involves students being active in finding solutions to everyday life problems. This study aims to analyze the increase in mathematical literacy skills and student learning independence through the PBL model. The research method used in this study is a systematic review method, namely identifying, evaluating, and concluding on research results that are similar to a particular research topic. Based on this research, it can be concluded that (1) The PBL model can improve mathematical literacy skills, (2) The PBL model can inscrease student learning independence.